فاعلية تطبيق لعبة الصور في تحسين إتقان المفردات العربية لدى طلبة الصف الحادي عشر بالمدرسة العالية - Aprilia, Bela; Syamsuddin, Naidin; Putra, Alfan (Al Ibrah: Journal of Arabic Language Education, 2020)
This research aims to determine the Arabic vocabulary abilities of eleventh grade students at Al-Falah Senior High School, Lemahabang, North Luwu after the implementation of the Picture Game. To determine the effectiveness of implementing the Picture Game and increasing the Arabic vocabulary mastery of eleventh grade students at Al-Falah Senior High School, Lemahabang, North Luwu. This type of research is classroom action research, the data collection methods are observation, field notes and tests. The results of this research are classroom action research conducted by researchers. It can be concluded that improving the Arabic vocabulary mastery of eleventh grade students at Al-Falah Senior High School, Lemahabang, North Luwu can be increased through the application of picture game. The use of picture game is said to be effective in improving the Arabic vocabulary mastery of eleventh grade students at Al-Falah Senior High School, Lemahabang, North Luwu. This can be proven by the increase in students' vocabulary mastery from cycle 1 to cycle II. The percentage of complete mastery of students' Arabic vocabulary in cycle I was 75% or 15 students out of 20 students and in cycle II there was an increase in students' vocabulary mastery, namely with a percentage of 100%. Thus, in cycle II the learning outcomes are said to be complete. تهدف هذه الدراسة لمعرفة قدرة إتقان المفردات العربية لطلبة الصف الحادي عشر بالمدرسة العالية الفلاح ليماه أبانغ لووو الشمالية بعد تنفيذ لعبة الصور. لمعرفة فاعلية تطبيق لعبة الصور وزيادة إتقان المفردات العربية لدى طلبة الصف الحادي عشر بالمدرسة العالية الفلاح ليماه أبانغ لووو الشمالية. نوع هذا البحث هو البحث الإجرائي الصفي، طريقة جمع البيانات هي الملاحظة و أسئلة الاختبار. نتائج هذا البحث هو البحث الإجرائي الصفي الذي أجراه الباحثة أن الزيادة في إتقان المفردات العربية لطلبة الصف الحادي عشر بالمدرسة العالية الفلاح ليماه أبانغ لووو الشمالية يمكن زيادتها من خلال تطبيق لعبة الصور. إن استخدام لعبة الصور فعال في زيادة إتقان المفردات العربية لطلبة الصف الحادي عشر بالمدرسة العالية الفلاح ليماه أبانغ لووو الشمالية. يمكن إثبات ذلك من خلال الزيادة في إتقان الطلبة للمفردات في الدورة الأولى  تبلغ نسبة اكتمال إتقان الطلبة للمفردات العربية في الدورة الأولى 75٪ أو ما يصل إلى 15 طالبة من أصل 20 طالبة وفي الدورة الثانية هناك زيادة في إتقان الطلبة للمفردات وهي نسبة 100٪.، في الدورة الثانية، يقال فإن نتائج التعلم كاملة. الكلمات المفتاحية: لعبة الصور، المفردات العربية، بحث اجرائي صفي